Dermal absorption and toxicity of alpha amanitin in mice. (June 2014) - Kaya, Ertugrul; Surmen, Mustafa Gani; Yaykasli, Kursat Oguz; Karahan, Selim; Oktay, Murat; Turan, Hakan; Colakoglu, Serdar; Erdem, Havva
Abstract The fungus Amanita phalloides is known to contain two main groups of toxins: amanitins and phallotoxins. The amanitins group effectively blocks the RNA polymerase II enzyme found in eukaryotic cells. As alpha amanitin has a lethal effect on the majority of eukaryotic cells, it can be valuable as an antiparasitic or antifungal drug. It can be used externally against ectoparasites. It is critical that percutaneous applications of the alpha amanitin toxin are not harmful to the recipient. In this study, the absorption and the toxicity of percutaneous and intraperitoneal (ip) applications of 1 mg/kg alpha amanitin to mice were compared. Potential skin, liver and kidney toxicities were investigated through pathological examination. HPLC analysis was used to determine the amount of the toxin. No toxicity or toxin were found in the skin, liver, or kidneys of the mice in the control group. Interestingly, the percutaneous application group also showed no toxicity, and the toxin was not present in this group. After 24 h, Councilman-like bodies and pyknotic cells were observed in the mice in which alpha amanitin was applied intraperitoneally, demonstrating the presence of toxicity. Peak levels of alpha amanitin (µg/mL) in the liver, kidney, and blood in the ip application group were measured at 3.3 (6 h), 0.2 (6 h) and 1.2 (1 h), respectively. The results demonstrated that the toxin was not absorbed through the skin of the mice and that the percutaneous application of alpha amanitin did not have any toxic effects. Thus, alpha amanitin may be administered percutaneously for therapeutic purposes.